Phosphate Solubilizing and Antifungal Activity of Root Endophyte Isolated from Shorea leprosula Miq. And Shoreal selanica (DC) Blume - Safinah Surya Hakim; Sri Wilarso Budi; Maman Turjaman (Institut Pertanian Bogor (IPB University), 2015)
Fungal endophytes are fungi that lives within plant tissues without causing apparent disease. It is also suggested that these fungi have ability to enhance plant growth and plant resistancy against pest and disease. This research is a preliminary study about root fungal endophytes in dipterocarp since there are lack research concerning about this study focus. We examined root fungal endophyte isolated from seedling of Shorea leprosula and Shorea selanica taken from Dramaga Experimental Forest, Bogor. Furthermore, we also tried to find out the fungal potential ability to solubilize phosphate and suppres fungal pathogen by in vitro assay. Surface sterilization method was used to isolated fungal endophytes from root tissues. Trichoderma spirale, Velsalceae sp., Melanconiela ellisii, Chaetosphaeria callimorpha, and Trichoderma asperellum were isolated during this study. These fungi appear to have specific association between fungal species and host plant, but no evidence of fungal order-level specificiation in S. leprosula and S. selanica. In vitro test also suggested that root fungal endophyte Trichoderma spirale and Melanconiella elisii have potential ability to solubilize inorganic phosphate. In addition, this result also present that root fungal endophyte T. spirale and T. asperellum have the potential to inhibit pathogen fungi Fusarium sp.